2016
DOI: 10.1038/srep31689
|View full text |Cite
|
Sign up to set email alerts
|

Live volumetric (4D) visualization and guidance of in vivo human ophthalmic surgery with intraoperative optical coherence tomography

Abstract: Minimally-invasive microsurgery has resulted in improved outcomes for patients. However, operating through a microscope limits depth perception and fixes the visual perspective, which result in a steep learning curve to achieve microsurgical proficiency. We introduce a surgical imaging system employing four-dimensional (live volumetric imaging through time) microscope-integrated optical coherence tomography (4D MIOCT) capable of imaging at up to 10 volumes per second to visualize human microsurgery. A custom s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 63 publications
(89 reference statements)
1
80
0
Order By: Relevance
“…A separate study corroborated these findings and reported that MIOCT altered decision-making in 41.9% of procedures [124]. Lastly, Carrasco-Zevallos et al first reported live 3D (4D) MIOCT of human retinal surgery [122,145,146], and this custom swept-source OCT system was demonstrated to produce B-scans of comparable quality to HHOCT imaging during surgical pauses [182]. In addition, 4D MIOCT provided enhanced volumetric feedback during live surgery, which facilitated recognition of 3D structural alterations after surgical intervention and enabled more complete visualization of surgical maneuvers (Fig.…”
Section: Human Retinal Surgerysupporting
confidence: 66%
See 4 more Smart Citations
“…A separate study corroborated these findings and reported that MIOCT altered decision-making in 41.9% of procedures [124]. Lastly, Carrasco-Zevallos et al first reported live 3D (4D) MIOCT of human retinal surgery [122,145,146], and this custom swept-source OCT system was demonstrated to produce B-scans of comparable quality to HHOCT imaging during surgical pauses [182]. In addition, 4D MIOCT provided enhanced volumetric feedback during live surgery, which facilitated recognition of 3D structural alterations after surgical intervention and enabled more complete visualization of surgical maneuvers (Fig.…”
Section: Human Retinal Surgerysupporting
confidence: 66%
“…This feature allowed a densely-sampled OCT scan to be re-centered to the site of interest in realtime after lateral translation of the microscope relative to the surgical field. Several MIOCT systems also employed independent OCT refocusing mechanisms in case the surgical field was shifted outside the OCT focus plane [117,121,122]. The electrically-controlled tunablefocus lens incorporated in [117] could also enable automatic focus adjustment.…”
Section: Optical Designs For Microscope-integrated Octmentioning
confidence: 99%
See 3 more Smart Citations